In-Substrate Resonators and Bandpass Filters with Improved Insertion Loss in K-Band Utilizing Low Loss Glass Interposer Technology and Superlattice Conductors (2016)
In this work, we report on in-substrate passive components using a high performance glass interposer and through glass via (TGV) technology and a multi-layer superlattice conductor architecture. Minimal RF loss is achieved using low dielectric loss glass substrates and superlattice conductors featuring skin effect suppression. Half mode substrate integrated waveguide (HMSIW) resonators and two-pole bandpass filters, embedded inside a glass interposer substrate, are used as test vehicles for the demonstration of insertion loss improvement in K-band. The utilized conductor is made of 20 layers of Cu/NiFe with each pair of 360 nm/30 nm, respectively, where NiFe layers with negative permeability in frequency range of interest are used for eddy current cancelling and improving the conductor loss. Control devices using the same glass substrate and conductor made of pure copper are fabricated for comparison purposes. The glass interposer substrate (SGW3, Corning Incorporated) has a thickness of 0.13 mm and the TGV's with a diameter of 0.08 mm. Up to 0.3 dB reduction in the insertion loss is achieved by using the proposed superlattice approach on glass substrates. © 2016 IEEE.